The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/2082351
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Structures in Differentially Coded Cardiovascular Time Series

Abstract: Objectives. This paper analyses temporal dependency in the time series recorded from aging rats, the healthy ones and those with early developed hypertension. The aim is to explore effects of age and hypertension on mutual sample relationship along the time axis. Methods. A copula method is applied to raw and to differentially coded signals. The latter ones were additionally binary encoded for a joint conditional entropy application. The signals were recorded from freely moving male Wistar rats and from sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…It was shown [ 49 ] that the delay of 0, 1, and 2 beats is the most appropriate for humans, while the delays of 3, 4 and 5 beats are appropriate for rats [ 29 ] and mice [ 47 ]. In [ 50 ], it was shown that, in laboratory rats, the highest level of comonotonic behavior of pulse interval and systolic blood pressure is observed at time lags 0, 3, and 4 beats, while a strong counter-monotonic behavior occurs at time lags of 1 and 2 beats.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown [ 49 ] that the delay of 0, 1, and 2 beats is the most appropriate for humans, while the delays of 3, 4 and 5 beats are appropriate for rats [ 29 ] and mice [ 47 ]. In [ 50 ], it was shown that, in laboratory rats, the highest level of comonotonic behavior of pulse interval and systolic blood pressure is observed at time lags 0, 3, and 4 beats, while a strong counter-monotonic behavior occurs at time lags of 1 and 2 beats.…”
Section: Methodsmentioning
confidence: 99%
“…A survey of Verapamil in literature includes the effect considering cardiac arrhythmias [17], atrial fibrillation [18] and mortality after myocardial infarction [19], but without the assessment of SBP and RRI linear and non-linear relationship using cross-entropy and copula in connection to the baroreflex sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous copula families exist, but pharmacological validation has shown that Frank copula is the most suitable choice for the cardiovascular signals [31]: it is unbounded and symmetric, it is equal to zero if the signals are statistically independent, it is more sensitive for SBP-PI signal changes than the other families of explicit and implicit copulas, and in SBP-PI case it models both the comonotonic and the countermonotonic dependence. Application examples of Frank copula in a context of SBP-PI relationship are shown in [32].…”
mentioning
confidence: 99%